2019
DOI: 10.1016/j.mec.2019.e00086
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-fusion strategies for redirecting and improving carotenoid synthesis in S. cerevisiae

Abstract: Spatial clustering of enzymes has proven an elegant approach to optimize metabolite transfer between enzymes in synthetic metabolic pathways. Among the multiple methods used to promote colocalisation, enzyme fusion is probably the simplest. Inspired by natural systems, we have explored the metabolic consequences of spatial reorganizations of the catalytic domains of Xanthophyllomyces dendrorhous carotenoid enzymes produced in Saccharomyces cerevisiae. Synthetic genes encoding bidomain enzymes composed of CrtI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Application of fusion proteins for carotenoid production has recently gained more interest. It has been shown that application of a tridomain protein comprising CrtB, CrtI and CrtY doubled β-carotene production by S. cerevisiae [26]. Both, the domain order and the linker properties, were claimed to influence the stability and/or expression of such enzymes [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of fusion proteins for carotenoid production has recently gained more interest. It has been shown that application of a tridomain protein comprising CrtB, CrtI and CrtY doubled β-carotene production by S. cerevisiae [26]. Both, the domain order and the linker properties, were claimed to influence the stability and/or expression of such enzymes [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that application of a tridomain protein comprising CrtB, CrtI and CrtY doubled β-carotene production by S. cerevisiae [26]. Both, the domain order and the linker properties, were claimed to influence the stability and/or expression of such enzymes [26]. Interestingly, the natural astaxanthin producer Xanthophyllomyces dendrorhous possesses bifunctional enzymes in carotenogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the CCD1 could be fused to the lycopene cyclase domain of the CrtYB, avoiding the access to other intermediates. A recent report of heterologous production of β-carotene in S. cerevisiae has shown promise for the optimization of carotenoids in yeast (Rabeharindranto et al, 2019).…”
Section: Genome-scale Stoichiometric Analysis Suggests Fyn-phccd1 Hasmentioning
confidence: 99%
“…The exact same coding sequences were used for cloning into pYeDP60 50 vector for S. cerevisiae expression, in association with a FLAG-tag instead of the previous hexahistidine-tag. We used YHR01 and YHR02 from Rabeharindranto et al 28 , using the protocol for yeast transforma- www.nature.com/scientificreports/ tion adapted from Gietz et al 51 . YHR01 and YHR02 correspond to S. cerevisiae BY4741 engineered for GGPP production (over-expression of GGPP synthase, CrtE, from P. rhodozyma and truncated form of HMG-CoA reductase, HMG1) 28 .…”
Section: Protein Purification Escherichia Coli Cells Lysis Was Perfomentioning
confidence: 99%
“…We used YHR01 and YHR02 from Rabeharindranto et al 28 , using the protocol for yeast transforma- www.nature.com/scientificreports/ tion adapted from Gietz et al 51 . YHR01 and YHR02 correspond to S. cerevisiae BY4741 engineered for GGPP production (over-expression of GGPP synthase, CrtE, from P. rhodozyma and truncated form of HMG-CoA reductase, HMG1) 28 . Phytoene production in YHR02 is mediated by the expression of bifunctional phytoene synthase/lycopene cyclase, CrtYB and in YHR01 thanks to the expression of the truncated form of CrtYB having only the phytoene synthase activity.…”
Section: Protein Purification Escherichia Coli Cells Lysis Was Perfomentioning
confidence: 99%